Development of the Epilepsy Risk Awareness scale (ERA scale) for people with epilepsy. (March 2017) - Braun, Andreas; Kendall, Sally; Cole, Christine; Smeeton, Nigel; Angus-Leppan, Heather
Highlights: People with epilepsy need the optimal balance of risk reduction and freedom from unnecessary restrictions. Assessment of people with epilepsy regarding their safety in daily life is recommended. The current Epilepsy Risk Awareness (ERA) scale refines the published Epilepsy Risk Awareness Checklist (ERAC). The ERA scale is a short quantified tool assessing the risk and safety profile in people with epilepsy Abstract: Purpose: Quality of life in people with epilepsy depends on balancing protection from risks and avoiding unnecessary restrictions. The Epilepsy Risk Awareness Checklist (ERAC) was developed to summarise an individual's safety, health care and quality of life and to facilitate communication between professionals. Although effective, the existing Checklist required quantification and shortening to increase its utility, particularly as a longitudinal tool for measuring and communicating changes over time. Methods: 5 clinical experts, 3 people with epilepsy and 5 carers assessed the importance of each item on the ERAC questionnaire in a two-round Delphi survey. The refined Epilepsy Risk Awareness scale (ERA scale) was piloted in 30 patients to obtain an overall and sub-scale score for personal safety, health care, and quality of life domains, and was compared with the validated Seizure Severity Scale and Epilepsy Self-Management Scale. Results: ERAC was shortened from 69 to 48 items to take 15–20 min for completion. Pilot results showed good internal consistency for the overall ERA scale, for the Personal Safety and Health Care subscales, but less for the Quality of Life subscale. There was strong association between ERA scale and the Epilepsy Self-Management Scale, but little relationship with Seizure Severity Scale scores, which focus on individual seizures. User ratings were high. Conclusions: The ERA scale has been shortened and quantified to provide an objective measure of the risks and safety profile in people with epilepsy. The scale will be further tested for intra-rater variability and utility.